The Effect of Project-Based Learning on Students’ Systematic Thinking Skills in Elementary Mathematics - Irnesari, Ella; Syarifudin, Syarifudin; Adiansha, Adi Apriadi (FKIP Universitas Lampung, 2025)
The purpose of this study is to evaluate the effect on the systematic reasoning capacity of elementary mathematics students of the Project-Based Learning (PjBL) model. The study consisted in a quasi-experimental design with an experimental group applying PjBL and a control group using conventional methods. Purposive sampling enabled participants to be chosen from several elementary schools. The Minimum Competency Assessment guided the method of data collecting by means of a systematic thinking skills test. The test consisted in essay questions covering students's capacity to identify patterns, develop plans, investigate conceptual links, and evaluate approaches of problem-solving. An observation notebook was also used to document student participation and activity all through the learning process. Among other statistical tests, paired and independent t-tests let one compare the pretest and posttest scores. From the data, higher posttest scores and statistically significant deviations exposed that students in the PjBL group showed a rather better improvement in systematic thinking than the control group. Additionally, the observation data demonstrated that PjBL students utilized analytical and reflective thought during the project operations, actively participated in peer-based conversations, and increased their participation. Through their connection between mathematical ideas and practical problems, these learning opportunities helped students to develop their structured thinking and evaluation skills. By providing contextual, meaningful, and cooperative learning, the results imply that PjBL is efficient in the evolution of higher-order thinking. In order to improve students' systematic thinking a ability necessary for both academic success and practical problem-solving teachers are therefore advised to include PjBL into mathematics education. Keywords: project-based learning, systematic thinking, mathematics learning.